Pengaruh Kompentensi, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Kantor Kejaksaan Negeri Konawe - Catrin Ruth Greys; Heriswanto Heriswanto (Jurnal of Management and Social Sciences, 2024)
This study aims to determine ''The Influence of Competence, Work Motivation and Job Satisfaction on the Performance of Employees at the Konawe District Attorney's Office'' The population in this study were all employees of the Konawe District Attorney's Office, totaling 41 people. Determination of the sample in this study was carried out by census, meaning that the entire population was sampled. The analytical tool used is multiple linear regression analysis. The results of this study indicate that the variable Competence Work Motivation and Job Satisfaction simultaneously have a significant positive effect. and the results show that partially the competence variable has a significant effect while Work Motivation and Job Satisfaction have no significant effect on the performance of the Konawe District Prosecutor's Office employees.